Aplicación de un sistema de costos por órdenes de producción de la textilera "CREACIONES BOXXTANA" por el año fiscal 2019. - Correa Mendoza, Nathaly Silvana (2020)
The objective of this integrative work is to apply a system of budgets for production orders for the texti e “Cre tions Boxxt n ” of Amb to city, which qu it tive nd qu ntit tive rese rch approach is used, accompanied by a bibliographic review to support the study variables and structure the theoretical framework, a field investigation was also developed in which a diagnosis was made through process mapping, an interview was applied, and the observation obtaining the following aspects as main findings: the topic of budgets are managed empirically, which causes the textile company to have problems when it comes to knowing its real situation, because unfortunately the company does not have a production cost system. Under this background, the pp ic tion of cost system for production orders for the “Cre ciones Boxxt n ” texti e comp ny was analyzed, evaluating the three elements of budget such as raw material, labor and indirect manufacturing budgets, of which the accounting technique for production orders express production that an allocation rate must be applied for each production order. Finally, it is also described by means of an example, the procedures and records of the main accounting transactions, pertinent to production, which have allowed us to know for sure the actual budgets incurred in the production process, the same ones that are reflected in the sheet of costs and in the state of products produced, allowing to know, the unit costs, the total costs and the percentage of utility that the company obtains production and subsequent sale of its products.